Potencialidades didáticas de textos e problemas históricos egípcios e babilônicos para o ensino de matemática na educação básica - PEREIRA, Patricia Sheila Figueiredo (Universidade Federal do Pará, 2022)
This research aimed to investigate which texts and historical problems present in the mathematics of Egypt and Babylon have didactic potentialities to be explored in the teaching of mathematics. For this, a bibliographical research was carried out in the literature of Boyer (1974) and Eves (2011), which provided the historical context of mathematics, as revealed several forms of solving ancient mathematical problems and that these are possible to be solved through the current notation. When studying the History of Mathematics, several potentialities that enable the development of mathematical skills were identified in the texts and historical problems that enable the development of mathematical skills, which were evidenced according to the arguments of Miguel (1997) and the studies of Mendes and Chaquiam (2016), Brandemberg (2020) and Brandemberg (2021), which corroborate the relevance of history in mathematics teaching. From this study, it was possible to select the texts of the Plimpton Table 322, the historical problems of the Rhind Papyrus and those of The BM Table 13901 as sources of/with potentialities, which are: to enable the conceptual development of the polynomial equation of the 1st degree; enable the development of the concept of the quadratic equation; to provide the student with new discourses on pythagoras' theorem and, with this, enable the development of skills foreseen in the National Common Curriculum Base (BNCC). In addition, it was suggested, through didactic activities, a way for the teacher to use the texts and historical problems in the teaching of school mathematics. Thus, it can be inferred that the selected texts and historical problems have potentialities that contribute to the construction of mathematical knowledge, as well as it was evidenced that they can be used in the process of teaching and learning mathematics in Basic Education.